Transcriptional regulation with CRISPR-Cas9: principles, advances, and applications. (August 2016) - Didovyk, Andriy; Borek, Bartłomiej; Tsimring, Lev; Hasty, Jeff
Graphical abstract: Highlights: CRISPR-Cas9 is a powerful tool to modulate transcription in wide range of cell types. An expanding set of CRISPR-based transcription effectors is available. Gene networks can be efficiently probed and modified for biotechnology applications. Abstract : CRISPR-Cas9 has recently emerged as a promising system for multiplexed genome editing as well as epigenome and transcriptome perturbation. Due to its specificity, ease of use and highly modular programmable nature, it has been widely adopted for a variety of applications such as genome editing, transcriptional inhibition and activation, genetic screening, DNA localization imaging, and many more. In this review, we will discuss non-editing applications of CRISPR-Cas9 for transcriptome perturbation, metabolic engineering, and synthetic biology.